Penyuluhan Pentingnya Pendidikan Bagi Anak di Dusun Sawahlega, Desa Pabuaran, Kecamatan Kemang, Kabupaten Bogor - Siti Faridah, Eva; Dahlan, Zaeni; Muttaqien, Mustika Dewi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2023)
Education is very important for children since they will be responsible for the progress of the nation and the country. However, in reality, many children still drop out of school, especially in Bogor Regency. The Dinas Pendidikan Kabupaten Bogor (Bogor Regency Education Office) noted that throughout 2021, a total of 1,884 children had dropped out of school. Responding to this fact, it is necessary to hold community outreach activities on the campaign of mainstreaming education for children in society. Based on the background mentioned above, the Islamic Religious Education and Early Childhood Islamic Education Study Program STAI Al-Hamidiyah Jakarta held community service activities in the form of counseling with the theme